2019
DOI: 10.1038/d41586-019-02872-2
|View full text |Cite
|
Sign up to set email alerts
|

A fairer way forward for AI in health care

Abstract: Artificial intelligence has great potential to improve health care, but without careful implementation, only a privileged portion of society will benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 5 publications
2
40
0
Order By: Relevance
“…healthcare costs) which did not provide the full picture regarding the health of black people [61]. Another example came from the University of Chicago hospital system, where researchers found that if postal codes had been used in their machine-learning algorithm to optimize hospital resources, resources available for black people would have been diverted towards "wealthy white people, exacerbating existing biases in the system" [62]. As residential segregation is also a known consequence of structural racism [63], this shows how structural racism can have many repercussions on algorithmic decisions in the healthcare system.…”
Section: Second Node: Integration Of Biased Health Data For Pm Initiamentioning
confidence: 99%
“…healthcare costs) which did not provide the full picture regarding the health of black people [61]. Another example came from the University of Chicago hospital system, where researchers found that if postal codes had been used in their machine-learning algorithm to optimize hospital resources, resources available for black people would have been diverted towards "wealthy white people, exacerbating existing biases in the system" [62]. As residential segregation is also a known consequence of structural racism [63], this shows how structural racism can have many repercussions on algorithmic decisions in the healthcare system.…”
Section: Second Node: Integration Of Biased Health Data For Pm Initiamentioning
confidence: 99%
“…Social justice Concerns about how these new technologies might affect the distribution of the benefits and burdens related to AI use in healthcare [3,9,16,17,19,[23][24][25][26][27][28][29].…”
Section: Parental Concerns Descriptionmentioning
confidence: 99%
“…Organizational excellence is defined as an effort to develop different processes and standards intended to engage employees to deliver excellent products [62]. Consequently, developers are authorized to update AI models without to review by the FDA [63]. However, a testing process must crucially be developed so that the updated models' performance is not below that of the primary models [64].…”
Section: Resultsmentioning
confidence: 99%
“…From China's perspective, AI is a powerful tool for economic success, military dominance, and controlling the population [72]. Chinese companies accumulate a tremendous amount of health-related data, which can be used in AI development, owing to lenient regulation on data collection and little public concern about data privacy [63,75]. However, in recent years, the Chinese public has started to petition large companies, such as Baidu and Alibaba, for the right to data privacy [75].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation